PENGARUH LINGKUNGAN KELUARGA TERHADAP PRESTASI BELAJAR PESERTA DIDIK KELAS IV MIS AL-HIKMA BALAURING KABUPATEN LEMBATA - Atapukan, Rahmawati Rusli; Syahrul, Muhammad; Kade, Samsuddin; Martini; Aidil Sudarmono R, Muh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to: (a) describe the condition of the students family environment, (b) describe the level of students learning achievement. And (c) analyze the influence of the family environment on students learning achievement. The family environment plays an important role as the first place where children receive education and support in the learning process. This study employs a quantitative approach to axemine the relationship between the family environment and student learning achievement. The population consists of 129 students from grades I to VI, with a sample of 24 fourth-grade students selected as research subjects. Data were collected through observartion, interviews, documentation, and questionnaires, then analyzed using descriptive quantitative analysis and statistical testing to determine the strength of the relationship between variables. The results show that: (a) the family environment condition is in the moderate category with an average score of 48,67. (b) the level of students learning achievement is an the low category with an average score of 32,25. (c) there is a significant influence between the family environment on students learning achievement. This is evidenced by a t-value of 4,029, which is greater than the t-table of 2,074 at a 5% significance level. The coefficient of determination of 42,40% indicates that the family environment contributes substantially to learning achievement.